2007
DOI: 10.1007/s12032-007-9005-3
|View full text |Cite
|
Sign up to set email alerts
|

Single agent gemcitabine in the second-line treatment of advanced non-small cell lung cancer after treatment with taxane + platinum regimens

Abstract: In this study, we investigated the activity of single agent gemcitabine in the second-line setting of non-small cell lung cancer (NSCLC). File records of 21 patients treated with single agent gemcitabine in advanced NSCLC who received one prior chemotherapy including a taxane and platinum combination were retrospectively evaluated. Treatment consisted of IV gemcitabine 1,250 mg/m2 on days 1 and 8, followed by a 1-week rest repeated every 3 weeks. A partial response was achieved in four (19%) patients. The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Coskun et al study,21 patients treated with single agent gemcitabine as a secondline treatment and reported a partial response rate 19%, stabil disease rate 29%, median OS was 36 weeks. Only one patients experienced grade ¾ hemathologic toxicity in this study (Coskun et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Coskun et al study,21 patients treated with single agent gemcitabine as a secondline treatment and reported a partial response rate 19%, stabil disease rate 29%, median OS was 36 weeks. Only one patients experienced grade ¾ hemathologic toxicity in this study (Coskun et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Treatment-related death wasn't observed. Non-hemathologic toxicities are summarized in Table that median OS 17 weeks to 10 months, RR 0-38% (Hainsworth et al, 1995;Androulakis et al, 1998;Socinski et al, 1999;Bonomi et al, 2005;Coskun et al, 2008;Paz-Ares et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, overall response rate was between 18.5% and 19% in the treatment of single agent gemcitabine as a second treatment (Cho et al, 2006, Coskun et al, 2008. Overall response rate was higher in the group receiving docetaxel (12% vs 8%) and PFS and OS were longer in the gemcitabine group (but not istatistically sagnificant).…”
Section: Discussionmentioning
confidence: 86%
“…60 Subsequent studies demonstrated that pemetrexed was as effective as docetaxel in the second-line setting but was less toxic. 61 Gemcitabine also may be of some value in this setting, 62 whereas vinorelbine appears to be ineffective. 63 Targeted Therapies in Non-Small Cell Lung Cancer Targeted therapies are based on the use of drugs or other agents that are directed specifically against a cell growth receptor or its ligands, signaling pathway components, or other effectors of function.…”
Section: Chemotherapy In Previously Treated Patients With Advanced Nomentioning
confidence: 99%